Arguing about justice - Axel Gosseries, Philippe Vanderborght (dir.) (Presses universitaires de Louvain, 2011)
This book brings together fifty of today's finest thinkers. They were asked to let their imaginations run free to advance new ideas on a wide range of social and political issues. They did so as friends, on the occasion of Philippe Van Parijs's sixtieth birthday. Rather than restricting themselves to comments on his numerous writings, the authors engage with the topics on which he has focused his attention over the years, especially with the various dimensions of justice, its scope, and its d...